Prognostic Value of Perineural Invasion in Oral Tongue Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis - Li, Jiajia; Liu, Shan; Li, Zhangao; Han, Xinxin; Que, Lin (Frontiers in Oncology, 2021)
Objectives: A significant number of recently published research has outlined the contribution of perineural invasion (PNI) to clinical outcomes in oral tongue squamous cell carcinoma (OTSCC), but some results remain conflicting. This study aimed to determine whether patients with OTSCC with PNI have a worse prognosis than those without PNI. Materials and Methods: PubMed, Embase, and Cochrane library were queried for potentially eligible articles published up to December 2020. The primary outcomes were the hazard ratio (HR) for locoregional recurrence, overall survival (OS), disease-free survival (DFS), and cancer-specific survival (CSS). The random-effect model was used in all analyses. Results: Seventeen studies (4445 patients) were included. Using adjusted HRs, the presence of PNI was associated with a higher risk of locoregional recurrence (HR=1.73, 95%CI: 1.07-2.79, P=0.025, I2=33.1%, Pheterogeneity=0.224), worse OS (HR=1.94, 95%CI: 1.39-2.72, P<0.001, I2=0.0%, Pheterogeneity=0.838), worse DFS (HR=2.13, 95%CI: 1.53-2.96, P<0.001, I2=48.4%, Pheterogeneity=0.071), and worse CSS (HR=1.93, 95%CI: 1.40-2.65, P<0.001, I2=25.5%, Pheterogeneity=0.251). PNI had an impact on locoregional recurrence in early-stage OTSCC but not in all stages, and on OS, DFS, and CSS in all-stage and early-stage OTSCC. The sensitivity analyses showed that the results were robust. Conclusion: The presence of PNI significantly affects the locoregional recurrence and survival outcomes among patients with OTSCC.